The Minimal Leak Test Technique for Endotracheal Cuff Maintenance. Issue 5 (September 2016) - Harvie, D. A.; Darvall, J. N.; Dodd, M.; De La Cruz, A.; Tacey, M.; D'Costa, R. L.; Ward, D.
Endotracheal tube (ETT) cuff pressure management is an essential part of airway management in intubated and mechanically ventilated patients. Both under- and over-inflation of the ETT cuff can lead to patient complications, with an ideal pressure range of 20–30 cmH2 O defined. A range of techniques are employed to ensure adequate ETT cuff inflation, with little comparative data. We performed an observational cross-sectional study in a tertiary metropolitan ICU, assessing the relationship between the minimal leak test and cuff manometry. Forty-five mechanically ventilated patients, over a three-month period, had ETT cuff manometry performed at the same time as their routine cuff maintenance (minimal leak test). Bedside nurse measurements were compared with investigator measurements. At the endpoint of cuff inflation, 20 of 45 patients (44%) had cuff pressures between 20 and 30 cmH2 O; 11 of 45 patients (24%) had cuff pressures <20 cmH2 O; 14 of 45 patients (31%) had cuff pressures >30 cmH2 O. Univariate analysis demonstrated an association between both patient obesity and female gender requiring less ETT cuff volume ( P =0.008 and P <0.001 respectively), though this association was lost on multivariate analysis. No association was demonstrated between any measured variables and cuff pressures. Inter-operator reliability in performing the minimal leak test showed no evidence of bias between nurse and investigators (Pearson coefficient = 0.897). We conclude the minimal leak test for maintenance of ETT cuffs leads to both over- and under-inflation, and alternative techniques, such as cuff manometry, should be employed.